Youth Migration and its Resultant Effect on Small-Scale Fish Farming in Southwest Nigeria - Segun, Ashley-Dejo Samuel (Food, Agriculture and Natural Resources - NETWORKS, 2024)
The study aimed at assessing the effects of rural youths’ migration pattern on small-scale fish farming in southwest Nigeria. Primary data were obtained from 440 fish farmers with the aid of a well-structured questionnaire, using multi-stage random sampling technique. Data collected were analyzed using descriptive statistics and likert scale rating techniques. The results showed that majority of the fishers were married males with mean age, household size and fishing experience of 44 years, 6 persons and 14 years respectively. It was further revealed that scarce employment opportunities (89.1%), flood/drought (85.7%), poverty (79.8%) and insurgency/displacement (75.5%) were the major push factors triggering rural youth’s migration in the study area while attractive wages/high income (98.0%), diverse employment opportunities (90.2%), alternative source of income during off season (86.1%) and availability of improved technologies (70.7%) were the major pull triggering youths’ migration in the study area. Thus, provision of loan to fishers at flexible interest rate, availability of improved fishing equipment, establishment of vocational training centres, integrating rural youth into empowerment programmes and provision of improved fishing methods to attract youth were the main strategies that could be used to checkmate rural youth migration in the study area. It was therefore recommended that Bank of Agriculture should be encourage to give out minimal loan interest rate to fishers at flexible repayment plans, empowerment/skills acquisition/entrepreneurship programmes should be established.